DEKONSTRUKSI MAKNA KEPEMIMPINAN PEREMPUAN PADA SURAT AN-NISA: 34 DAN I TIMOTIUS 2:12 (ANALISIS KOMPARATIF) - Ilmi , Vika Wafa; Syo Im, Noer (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
This research aims to deconstruct the meaning of women’s leadership in the view of Surah an-Nisa: 34 and I Timothy 2:12. This study is qualitative research. The data sources in this study come from the Qur’an printed by the Ministry of Religious Affairs and Bible printed by the Indonesian Bible Institute. The results of this research show that many people use Surah an-Nisa verse 34 and Timothy 2:12 as an argument that women are prohibited from leading. Interpretation of verses must look at the context. So it is important to deconstruct these texts to understand their meaning more broadly and inclusively. Through deconstruction analysis, we see that Surah an-Nisa verse 34 cannot be used as an excuse that women are not given the opportunity to become leaders so that women do not experience discrimination because of their status in the home or public sphere. Whereas in 1 Timothy 2:12, it is clear that in the context Paul does not prohibit women from becoming leaders of fellowships or churches. Therefore, women’s leadership in churches and other institutions remains relevant today. Because the Qur’an and the Bible do not teach gender discrimination.